FAKTOR – FAKTOR YANG MEMPENGARUHI KEJADIAN EKSTRAVASASI INFUS PADA PASIEN ANAK - Marleni, Lela; Novayelinda, Riri; Dewi, Ari Pristiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Infusion therapy was one of the most commonly used measure patients in hospitalization. One of the complications infusion therapy was extravasation. This studied determine affect factors the incidence extravasation infusion in pediatric patients. Research used descriptive correlative. The sample of this research was children treated and installed infusion in space Merak 1 RSUD Arifin Achmad Riau Province which amounted to 38 respondents. Results this studied showed that most of the infected children were extravasated (44.7%) and affected factors extravasation were therapy (p value = 0,000), fluid osmolarity (p value = 0,000), location installation of infusion (p value = 0.011) and number of infusions (p value = 0,000). It was also known there no correlation between age (p value = 0,192), gender (p value = 0,770), size IV chat (p value = 0,132) and nutrition (p value = 0,828) with extravasation in child. This studied suggested nurses to be able conducted further research on intravenous antibiotik dilution techniques so as to prevent extravasationKeywords: extravasation, fluid osmolarity, infusion, infusion stabbing, infusion site location and intravenous therapy